DEVELOPMENT OF STRATEGY AND PUBLIC COMMUNICATION FOR ISLAMIC BROADCASTING IN THE DIGITAL ERA - ALTRUIS BIZURAI CHILLYNESS (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
ABSTRACT This article comprehensively examines the concepts, theories, and practices of developing public communication strategies in Islamic broadcasting in the digital era. The study begins with an explanation of the theoretical foundations of public communication according to leading scholars, the basic concepts of Islamic broadcasting, and the integration of both within the context of contemporary digital media. Using a systematic literature review method focusing on scholarly publications from 2020–2025, this article analyzes the paradigm shift in da’wah communication from conventional to digital models and identifies effective strategies for reaching modern audiences. The findings indicate that public communication in Islamic broadcasting requires a holistic approach that integrates mass communication theories (agenda-setting, uses and gratifications), new media theories (interactivity, convergence), and the principles of Islamic da’wah. Key strategies include: (1) creative content grounded in authentic Islamic values, (2) consistent messaging with contextual relevance, (3) the use of analytic data for audience targeting, (4) collaboration with religious influencers, and (5) strengthening digital literacy among da’i. This article contributes to the development of a theoretical–practical framework for public communication in Islamic broadcasting that is adaptive to the dynamics of modern communication technologies while preserving the essential values of Islamic da’wah. Keywords: Public Communication, Islamic Broadcasting, Da’wah Strategy, Digital Media, Mass Communication.